Spin-qubit control with a milli-kelvin CMOS chip - Samuel K. Bartee; Will Gilbert; Kun Zuo; Kushal Das; Tuomo Tanttu; Chih Hwan Yang; Nard Dumoulin Stuyck; Sebastian J. Pauka; Rocky Y. Su; Wee Han Lim; Santiago Serrano; Christopher C. Escott; et al. (Nature, 2025)
Abstract A key virtue of spin qubits is their sub-micron footprint, enabling a single silicon chip to host the millions of qubits required to execute useful quantum algorithms with error correction1–3. However, with each physical qubit needing multiple control lines, a fundamental barrier to scale is the extreme density of connections that bridge quantum devices to their external control and readout hardware4–6. A promising solution is to co-locate the control system proximal to the qubit platform at milli-kelvin temperatures, wired up by miniaturized interconnects7–10. Even so, heat and crosstalk from closely integrated control have the potential to degrade qubit performance, particularly for two-qubit entangling gates based on exchange coupling that are sensitive to electrical noise11,12. Here we benchmark silicon metal-oxide-semiconductor (MOS)-style electron spin qubits controlled by heterogeneously integrated cryo-complementary metal-oxide-semiconductor (cryo-CMOS) circuits with a power density sufficiently low to enable scale-up. Demonstrating that cryo-CMOS can efficiently perform universal logic operations for spin qubits, we go on to show that milli-kelvin control has little impact on the performance of single- and two-qubit gates. Given the complexity of our sub-kelvin CMOS platform, with about 100,000 transistors, these results open the prospect of scalable control based on the tight packaging of spin qubits with a ‘chiplet-style’ control architecture.